Disrupsi Diri Pustakawan Era Industri 4.0 Perspektif Kitab Sarasamucaya - I Gusti Ayu Ketut Yuni Masriastri (Tampung Penyang, 2023)
Libraries as one of the institutions managing information sources keep up with the times and are dominated by shifts in science and technology. This is the influence of current trends and global developments as well as the information needs of library visitors. To achieve this, self-disruption of libraries and librarians must be implemented. The disruption referred to here is that libraries and librarians open themselves to changes caused by the very rapid development of digital technology. Apart from self-disruption, increasing the competence of librarians also plays an important role in dealing with digital technology. This study aims to describe the application of Hindu values ​​in the Sarasamuccaya book to the ethics and morals of librarians in working to face the disruption of the digital technology industry 4.0. This is contained in several sloka, namely: sloka 58, sloka 60 and sloka 62. This study is library research on research results and books that are relevant to the disruption of librarians towards digital industry 4.0. Library research is defined as a theoretical study, the object of which is references or other scientific literature such as books that are related to the study being carried out.